2017
DOI: 10.1021/jacs.7b05116
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Generated Thiyl Free Radicals Observed by X-ray Absorption Spectroscopy

Abstract: Sulfur-based thiyl radicals are known to be involved in a wide range of chemical and biological processes, but they are often highly reactive, which makes them difficult to observe directly. We report herein X-ray absorption spectra and analysis that support the direct observation of two different thiyl species generated photochemically by X-ray irradiation. The thiyl radical sulfur K-edge X-ray absorption spectra of both species are characterized by a uniquely low energy transition at about 2465 eV, which occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…This sensitivity is reflected in sulfur-1s transitions shifting much more substantially than in other atoms upon changes in the binding state of the respective sulfur atom. Combining this spectral fingerprint of sulfur chemistry with time-resolved measurements and electronic structure calculations (RASSCF, DFT) yields a powerful method to follow sulfur chemistry with elemental specificity. In previous studies by Kennepohl and co-workers, static X-ray absorption spectroscopy was used to investigate radiation damage and photochemistry in biomolecules and smaller biologically relevant molecules. , Another steady-state spectroscopic study of frozen solution and of room-temperature powder samples by Sneeden et al has identified signatures of sulfur-centered radicals generated by hard X-ray exposure on a time scale of minutes to hours . These very long-lived species provide valuable information for crystallography and X-ray scattering of molecules in amorphous and crystalline solids subjected to hard X-ray photons.…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity is reflected in sulfur-1s transitions shifting much more substantially than in other atoms upon changes in the binding state of the respective sulfur atom. Combining this spectral fingerprint of sulfur chemistry with time-resolved measurements and electronic structure calculations (RASSCF, DFT) yields a powerful method to follow sulfur chemistry with elemental specificity. In previous studies by Kennepohl and co-workers, static X-ray absorption spectroscopy was used to investigate radiation damage and photochemistry in biomolecules and smaller biologically relevant molecules. , Another steady-state spectroscopic study of frozen solution and of room-temperature powder samples by Sneeden et al has identified signatures of sulfur-centered radicals generated by hard X-ray exposure on a time scale of minutes to hours . These very long-lived species provide valuable information for crystallography and X-ray scattering of molecules in amorphous and crystalline solids subjected to hard X-ray photons.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur-containing radicals like thiyl radicals R-S•, sulfinyl radicals R-SO•, sulfonyl radicals R-SO 2 •, and sulfonyloxyl radicals R-SO 3 • are highly relevant to atmospheric chemistry, biology, and organic synthesis. For instance, simple sulfinyl radicals HSO• and CH 3 SO• , form as fleeting intermediates in the oxidation of volatile organic sulfur compounds (VOSCs) in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…As dithiane has been proposed as a model system for the disulfide moiety in proteins these conclusions have some transferability to expected protein chemistry. The buildup of significant kinetic energy upon internal conversion in the femtosecond time‐scale is expected to fracture the disulfide bonds in proteins to such a degree that the sulfur‐radicals formed will not recombine in line with what has recently been proposed by Sneeden et al . Instead the sulfur radicals may combine with similarly formed sulfur radicals to form new tertiary structures, or abstract hydrogen radicals to form peroxides in vivo, providing a new route for UV‐light to damage the organism.…”
Section: Resultsmentioning
confidence: 63%